The South China Sea Issue: Its Implications on South East Asian Security - K.C., Khadga (Journal of International Affairs, 2016)
Although the Chinese government has a strong preference for bilateral diplomatic negotiations to resolve disputes, its status as a party to UNCLOS and its continuing failure to reach a settlement with the Philippines has exposed it to the risk of litigation. Additionally, if the arbitration goes forward, China may be at a disadvantage because several Chinese assertions about their South China Sea rights are not well supported in international law. China’s leaders may also have concerns about avoid nationalists who are sensitive to any perception that the government lost control of a high profile issue to a small Southeast Asian state and a Japanese judge. Nonetheless, now that the Chinese have rejected the process, the panel will proceed without them, providing a small “victory” for Manila and potentially swinging international public opinion toward the Philippines. China being an established regional power and aspiring global power would better show her generosity to take the countries in neighborhood in confidence. For this, resolving South China Sea issue by win-win strategy will be of great benefit for regional stability and security in South East Asian region.